Glucose-triggered in situ forming keratin hydrogel for the treatment of diabetic wounds. (15th April 2021) - Chen, Yansong; Li, Ying; Yang, Xuexia; Cao, Zhangjun; Nie, Huali; Bian, Yonggang; Yang, Guang
Abstract: The development of protein-based in situ forming hydrogel remains a big challenge due to the limited chemical groups in proteins. Keratins are a group of cysteine-rich structural protein found abundant in skin and skin appendant. Recently, our lab has established a disulfide shuffling strategy to prepare keratin hydrogels via oxygen (O2 ) oxidation. However, such hydrogel still needed to be molded in advance. In this work, inspired by the fact that glucose commonly exists in body fluids, a glucose-triggered in situ forming keratin hydrogel was developed based on the disulfide shuffling strategy via a higher oxidation force of hydrogen peroxide (H2 O2 ). The hydrogel precursor solution consisted of keratin, cysteine and glucose oxidase (GOD), which could generate H2 O2 in an indirect and mild way via GOD-catalyzed oxidation of glucose in body fluids. Our findings demonstrated that the GOD-catalyzed oxidation method not only shortened the gelation time but improved the mechanical strength of the hydrogel by comparison with O2 oxidation and direct addition of H2 O2 solution methods, and realized in situ gelation within 3 min on a full-thickness wound bed in normal mice. Moreover, the in situ forming keratin hydrogel was applied as a drug depot for wound repair, and the deferoxamine-loaded one accelerated healing in the full-thickness wounds of streptozotocin-induced diabetic rats, notably by promoting angiogenesis and neovascularization in wounds. Statement of Significance: Studies show that keratin hydrogels possess tissue regeneration capacity, especially in skin wound repair. However, most of the reported keratin hydrogels needed to be molded in advance and cannot fit irregular wound shape. This work describes a glucose-triggered in situ forming keratin hydrogel via a disulfide shuffling strategy under the oxidation of hydrogen peroxide. Of note, the hydrogen peroxide was supplied indirectly by glucose oxidase-catalyzed oxidation of glucose in wound fluids, and this method needed no additional crosslinking agents or chemical modifications on keratins. Our findings showed that this hydrogel realized in situ gelation within 3 min on a full-thickness wound bed and enabled an injectable mode with good filling ability toward irregular wounds. Moreover, this hydrogel could be applied as a drug depot for the treatment of diabetic wounds.